Pengembangan Aplikasi Perangkat Bergerak Sistem Informasi Event di bidang Teknologi Informasi berbasis Android - Ilham Dwi Muchlison; Agi Putra Kharisma; Issa Arwani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Information technology events are activities organized by a group that focuses on science in the field of information technology. Based on the results of a survey conducted to 103 people who have attended events in the field of information technology and are over 17 years old, the results show that 71.8 percent of respondents have experienced difficulties in obtaining information on events in the field of information technology with the desired topic. 78.6 percent of respondents have missed an event they wanted to attend before because they forgot it. 92.2 percent of respondents, they need an application where give the information in the field of information technology that includes category division and reminders of events to be attended. Therefore, an application was made that connects event organizers in the field of information technology with people who have an interest in the field of information technology. Applications are developed using the Kotlin programming language, data storage using Firebase services, and using architectural patterns in Clean Architecture. In black-box testing, the results are 100% valid. In compatibility testing, it can be seen that the application can be used on devices with the Android operating system with versions of API 23 to API 30. In usability testing with an alpha level value of 10%, the average actual value is 86.5 Â± 4.5 for the application event finder and 89 Â± 5.1 for the event organizer application which means the application can be received well.